Integration of Chatting Technology in the Tandem Language Exchange Learning Process - Jamin Ambas; Yohana S. Touwe; Syilvia Wenny J; Dahlan Abdullah (Yayasan Adra Karima Hubbi, 2023)
Background. 21st century learning demands the integration of technology to meet the demands of current developments. In the context of language learning, Tandem Language Exchange is a modern method that stands out by utilizing chat technology. Purpose. The main aim of this research is to evaluate the impact of tandem chat integration in Tandem Language Exchange on students' language skills. In addition, this research aims to provide practical guidance for the development of innovative language learning approaches using chat technology, by contributing to understanding the potential of chat technology in language learning. Method. This research uses a quantitative approach with a survey model. Respondents consisted of English and Arabic primary language students at various universities in Indonesia. The survey results were analyzed using the Miles Huberman model and presented in chart form. Results. Of the 30 respondents, the majority of students felt significant benefits from integrating chat technology in language learning. The frequency of use of Tandem Language Exchange is quite high, reflecting students' active interest and involvement. Apart from that, the survey results also show that students' comfort level in using chat technology is generally positive, with the majority feeling comfortable or very comfortable. Conclusion. The integration of chat technology in Tandem Language Exchange has an overall positive impact, supporting the development of language skills and motivating students to be actively involved in the learning process. Despite some reported obstacles, high acceptance shows the great potential of using chat technology in language learning contexts in this digital era. Future recommendations could focus on improving guidance and support to ensure the use of chat technology is more effective and satisfying for students.